The Effectiveness of E-Learning as Teaching Media in EFL Classroom - Desi Surayatika (Universitas Indo Global Mandiri, 2019)
ABSTRACTThis research was made based used non-equivalent control group design that was conducted University of Indo Global Mandiri Palembang. The aim of this research was to find out the effectiveness of e-learning as teaching media in EFL classroom. In this research, there were two different samples to be judged their writing achievement. First is experimental group which was given a treatment and second is control group which was not given any treatment. As data source, a test in written test was used in this research. Before starting the research, a pre-test was taken from both groups and two raters scored the students’ written tests based on rubric score. After implementing the treatment, both groups were given a post-test and the same raters scored their tests to know the significant improvement and significant difference between the scores of both goups. The results indicated that by using this technique, the students’ writing achievement was improved. It was shown from the mean scores of pre-test in experimental group that increased from 43,30 to be 77,20 in post-test. The significant difference of the post-test scores between both of experimental and control groups could be seen from the results of the t-obtained of both groups. It was considered higher than the t-table. Accordingly, it could be claimed that teaching writing by using e-learning brought about an improvement in students’ writing achievement. This technique was good way to help students learning English.Keywords : improving, e-learningABSTRAKPenelitian ini di buat berdasarkan penelitian desain kelompok control tidak setara yang dilakukan di Universitas Indo Global Mandiri Palembang. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan menulis siswa dengan menerapkan e-learning. Dalam penelitian ini, ada dua sampel yang berbeda untuk dinilai pada kemampuan menulis siswa. Pertama adalah kelompok eksperimen yang diberi perlakuan dan yang kedua kelompok control yang tidak diberi perlakuan. Sebagai sumber data, tes dalam bentuk tertulis digunakan dalam penelitian ini. Sebelum memulai penelitian, pre-test diambil dari kedua kelompok dan dua penilai menilai kemampuan berbicara siswa berdasarkan skor rubrik menulis. Setelah menerapkan pengajaran, kedua kelompok diberi post-test dan penilai yang sama menilai kemmpuan menulis siswa untuk mengetahui peningkatan yang signifikan dan perbedaan yang signifukan antara skor kedua kelompok. Hasil menunjukkan bahwa dengan menggunakan teknik ini, kemampuan menulis siswa meningkat. Hal itu di tunjukkan dari nilai rata-rata pre-test pada kelompok eksperimen yang meningkat dari 43,30 menjadi 77,20 pada saat post-test. Perbedaan yang signifikan pada saat post-test antara kedua kelompok eksperimen dan control dapat dilihat dari hasil t-hitung. Nilai tersebut dianggap lebih tinggi dari t-tabel. dengan demikian, dapat dikatakan bahwa mengajar kemampuan menulis dengan menggunakan e-learning meningkatkan kemampuan menulis siswa. Teknik ini adalah cara yang baik untuk membantu siswa belajar bahasa inggris.Kata kunci : peningkatan, e-learning